2022
DOI: 10.3390/ijms231911904
|View full text |Cite
|
Sign up to set email alerts
|

Hair-Growth-Promoting Effects of the Fish Collagen Peptide in Human Dermal Papilla Cells and C57BL/6 Mice Modulating Wnt/β-Catenin and BMP Signaling Pathways

Abstract: Fish-derived collagen has recently emerged as an alternative collagen source with bioactive properties, including the enhancement of hair and skin health. It is also cost-effective and has high bioavailability, in addition to having fewer side-effects compared to collagen from porcine skin or bovine skin. Collagen peptides (CPs) extracted from the scales of Mozambique tilapia (Oreochromis mossambicus) reportedly promote hair and skin health. This study sought to evaluate the effects of CPs on hair growth using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…An antagonistic competition instead of simply a balanced interaction between BMP and Wnt signaling has been confirmed in stem cell . Previous reports have shown that TGF-β, as a paracrine mediator released by the DPCs through this signaling pathway, inhibits the proliferation of epithelial cells and the morphogenesis of HF, and instructs the transition of HFs from the anagen to the catagen. ,, Many drugs that promote hair restoration have shown activation of this pathway. ,, Interestingly, two phases with different BMP levels in the dermis are independent of telogen, whereas the phase with high BMP is more refractory to recover . BMP signaling controls the cohort of melanocyte maturation genes by activating LEF1 throughout the hair pigmentation, which is a key perspective for the treatment of hair graying …”
Section: Signaling Pathways and Common Drugs In Diseasesmentioning
confidence: 97%
See 2 more Smart Citations
“…An antagonistic competition instead of simply a balanced interaction between BMP and Wnt signaling has been confirmed in stem cell . Previous reports have shown that TGF-β, as a paracrine mediator released by the DPCs through this signaling pathway, inhibits the proliferation of epithelial cells and the morphogenesis of HF, and instructs the transition of HFs from the anagen to the catagen. ,, Many drugs that promote hair restoration have shown activation of this pathway. ,, Interestingly, two phases with different BMP levels in the dermis are independent of telogen, whereas the phase with high BMP is more refractory to recover . BMP signaling controls the cohort of melanocyte maturation genes by activating LEF1 throughout the hair pigmentation, which is a key perspective for the treatment of hair graying …”
Section: Signaling Pathways and Common Drugs In Diseasesmentioning
confidence: 97%
“…Representative drugs: minoxidil, exosomes, , valproic acid, , lithium, necrostatins, and KY19382. , …”
Section: Signaling Pathways and Common Drugs In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, fish‐derived collagen has emerged as an alternative and interesting source with bioactive properties. Indeed, fish‐derived HC presents some advantages such as low toxicity, low inflammatory responses, better absorbability, environmental friendliness, and less regulatory and quality control problems 12 . Although there is a weak evidence supporting their use, also micronutrients could be involved in hair loss management 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, fish-derived HC presents some advantages such as low toxicity, low inflammatory responses, better absorbability, environmental friendliness, and less regulatory and quality control problems. 12 Although there is a weak evidence supporting their use, also micronutrients could be involved in hair loss management. 13 Iron represents an essential element involve in different human function such as red blood cells production, function of enzymes and transcription factors, and DNA synthesis.…”
Section: Introductionmentioning
confidence: 99%